The spatiotemporal effects and drivers of industrial agglomeration—A case study of counties in the Yellow River basin - Duan, Ye; Zhao, Huimin; Zhang, Hao; Qin, Yuming; Han, Zenglin (Frontiers in Environmental Science, 2022)
While the research on industrial agglomeration has received more attention, there has been little research on its spatial effect and impact mechanism from the micro perspective. On the basis of the industrial cluster data of 600 counties in the Yellow River Basin (YRB) from 2010-2020, this article investigates the spatial effect of industrial agglomeration in the YRB from the two aspects of time and space via center-of-gravity analysis and exploratory spatial data analysis, and uses spatial econometric method to research the drivers of county-level industrial agglomeration. The results reveal the following. During the study period, the industrial center of gravity in the YRB presented a moving tendency from east to west, and 2016 was an important turning point. The county-level industrial distribution in the YRB showed an unbalanced trend, but its unbalanced degree exhibited a weakening trend. In terms of the temporal dimension, the county-level industrial agglomeration degree in the YRB presented a significant downward trend and emerged an evolution process of "diffusion-agglomeration-re-diffusion." Specifically, it gradually diffused from Shandong and Henan to southern Shanxi and Shaanxi. In the spatial dimension, the county-level industrial agglomeration in the YRB was found to have conspicuous spatial autocorrelation, and spatial spillover effect was prominent. The number of counties with high-high cluster gradually increased and shifted to the west, while the number of counties with low-low agglomeration exhibited a decreasing trend. The degree of government intervention restrains county-level industrial agglomeration, while the external industry level, regional market demand, and urbanization level promote county-level industrial agglomeration. In terms of river basins, in the upstream, the degree of government intervention and industrial structure adjustment inhibit industrial agglomeration, while the regional market demand and urbanization level promote industrial agglomeration. In the midstream, the degree of government intervention inhibits industrial agglomeration, while the external industry level, regional market demand and industrial structure adjustment promote industrial agglomeration. In the downstream, the external industry level and industrial structure adjustment restrain industrial agglomeration, while the regional market demand and urbanization level promote industrial agglomeration. The conclusions provide a significant reference for the industrial transformation and high-quality economic development of the YRB.